Identifikasi Pengelolaan Usaha Wisata Health And Wellness Di Samadi International Bali - Putri, Jasmine Nabila; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2024)
This research is motivated by the growing global trend of Health and Wellness tourism. The continuously expanding tourism sector offers various activities for incoming tourists. Bali is one of the cities in Indonesia that offers many Health and Wellness attractions, and one of the popular destinations in the Canggu area is Samadi International Bali. This study utilizes qualitative data obtained through interviews, observations, documentation, and literature review. The analysis technique employed is qualitative data analysis, which involves analyzing data collected from qualitative records. The results of the research indicate that Samadi International Bali offers a variety of tourism products with high potential for continuous growth. These products include yoga classes, wellness workshops, organic food markets, and holistic health treatments, which attract a diverse group of health-conscious tourists. Moreover, the study identifies various factors that influence the management of the tourism business at Samadi International Bali. Positive factors, such as the high demand for wellness services and the reputation of Bali as a health tourism destination, can be further developed and maintained. On the other hand, factors that cannot be changed, such as local regulations and economic fluctuations, require innovative strategies to ensure the business's sustainability. The management at Samadi International Bali has been proactive in adapting to these challenges by continuously updating their service offerings and incorporating feedback from visitors to enhance their experience. Overall, Samadi International Bali exemplifies a successful model in Health and Wellness tourism by leveraging its diverse offerings and adapting to various influencing factors. The findings suggest that with strategic development and innovative approaches, similar destinations can achieve sustained growth and enhance their appeal in the competitive tourism market. This research highlights the importance of continuous innovation and adaptability in the ever-evolving tourism industry. Keywords: Health and Wellness; Management; Tourism Business